ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR DI BIDANG INDUSTRI BARANG KONSUMSI - Dion Dewa Barata; Ferdinand Nainggolan; Muhammad Ilham Prabowo; Bella Febiola (Program Sarjana Manajemen Universitas Internasional Batam, 2022)
Determine the financial performance of manufacturing companies in the consumer product industry sector listed on the Indonesia Stock Exchange for the year 2019 through 2021 is the goal of this study. Financial ratios, such as liquidity ratios, solvability ratios, and profitability ratios are utilized in the quantitative analysis of the data used. All manufacturing businesses that were listed on the Indonesia Stock Exchange between 2019 until 2021 make up the population of this research. The manufacturing firm in the consumer products industry sector, which is part of the LQ45 category, served as the study's sample. The findings indicated that PT. Indofood CBP Sukses Makmur Tbk had the best financial performances in terms of corporate liquidity. In terms of debt to equity ratio, PT. Indofood Sukses Makmur Tbk, have the best financial results. PT Unilever Indonesia Tbk, nevertheless, has the best financial results in terms of profitability.